Water pollution in Malaysia: penalties under the Environmental Quality Act 1974 - Abdullah @ Abd Halim, Mohd Zulhelmey; Abu Bakar, Syatirah; Roslim, Salmah (Universiti Teknologi MARA, Kedah, 2025)
Water pollution is a significant issue in Malaysia and has serious implications for biodiversity, humans, and the economy. The country's growing industry, urbanisation, and agricultural activities have increased river, lake, and other water body pollution, negatively affecting the environment and the people. The Environmental Quality Act 1974 is the most important legal tool that Malaysia has employed, particularly in regulating wastewater. This Act is a set of rules that enforce control mechanisms against water pollution by establishing water quality standards, liability of offenders, and stringent punishment by way of penalty for an infraction of the law. Court decisions have also influenced how Malaysia’s water pollution laws are enforced.